Emergy diagnosis and reflections towards Brazilian sustainable development - Giannetti, B. F. [UNESP]; Demetrio, J. F. C. [UNESP]; Bonilla, S. H. [UNESP]; Agostinho, F. [UNESP]; Almeida, C. M. V. B. [UNESP] (Elsevier B.V., 2013)
This paper presents an environmental emergy-based diagnosis of Brazil compared with Russia, India, China, South Africa and United States. Reflections on the Brazilian sustainable development are presented and discussed based on the evaluations published since 1979. The variation of the emergy per capita for Brazil from 1979 to 2007 indicates that the country's growth is tied to the exploitation of non renewable natural resources which do not directly reflect in the welfare of the population. The total emergy exported per unit of gross domestic product increased in the period, suggesting that the country exports more emergy than that contained in the money received for the exportation. With the help of the emergy indices, the future development of Brazil is explored and discussed. The comparison among the BRICS (Brazil, Russia, India, China and South Africa) countries and United States indicates that what may be appropriate and usable within one country may not be within another and that to achieve the global sustainability two concomitant actions may occur: (i) the reduction of the total emergy use in developed economies, and (ii) the reduction of indigenous resources exportation in developing economies. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Development scenarios; Emergy ternary diagram; BRICS